Effet des eaux usées sur la biologie d’un bio indicateur animal de la famille des Lombricidae - Djeridi Imen; Oulguima Rifka (My University, 2023)
Most studies of the effects of pollutants on soil communities have been localized on earthworms which are therefore considered as bio -indicators of the health status of ecosystems. This work was undertaken with the aim of studying in vitro the effect of water commonly used in agriculture on weight gain, mortality and biochemical parameters (total protein, total carbohydrates, lipids total and CAT) as biomarkers of oxidative stress, in a model biological Aporrectodea trapezoides The physicochemical analysis of the soil showed that the latter is suitable for life earthworms, rich in organic matter 12.9%, of sandy-loamy texture with a neutral pH. Sewage Caused Remarkable Earthworm Weight Drops treated with wastewater compared to controls. According to our toxicity results, no significant mortality was recorded throughout the experimental period, Treatment of earthworms with wastewater has shown an increase total protein, total carbohydrates and total lipids after 72 h On the other hand, the CAT catalase activity did not show its enzymatic induction during the three treatment periods. -------------------------------------------------------------------------------------------------------------------------------------------------------------------- ركزت معظم الدراسات حول تأثيرات الملوثات على مجتمعات التربة مثل ديدان الأرض، والتي تعتبر مؤشرات بيولوجية للحالة الصحية للنظم البيئية. تم انجاز العمل الحالي مختبريا. لتبيانتأثير مياه الصرف الصحي التي تستخدم في الزراعة على بيولوجيا ديدان الأرض (الوزن ومعدل الوفيات،المعلمات البيو كيميائية"البروتينات الكلية، الكربوهيدرات الكلية، الدهون الكلية والكتلاز ").CAT كعلامات حيوية للإجهاد التأكسدي، في نموذج بيولوجي( Aporrectodea trapézoîdes). أظهر التحليل الفيزيائي والكيميائي للتربة أن هذه الأخيرة مناسبة لحياة ديدان الأرض، كونها غني بالمواد العضوية 12.9٪، وقوامها رملي طيني بدرجة حموضة متعادلة. تسببت مياه الصرف الصحي في حدوث انخفاض ملحوظ في وزن ديدان الأرض المعالجة بمياه الصرف الصحي مقارنةً بالشواهد. وفقًا لنتائج السمية لدينا، لم يتم تسجيل وفيات خلال فترة التجربة بأكملها. اظهرت معالجة ديدان الأرض بمياه الصرف ارتفاع في معدل البروتين الكلي والكربوهيدرات الكلية والدهون الكلية خصوصا بعد 72 ساعة. من ناحية أخرى، لم يُظهر نشاط الكاتلاز CAT تحريضه الإنزيمي خلال فترات التجربة الثلاثة. ------------------------------------------------------------------------------------------------------------------------------------------------------------------ Most studies of the effects of pollutants on soil communities have been localized on earthworms which are therefore considered as bio -indicators of the health status of ecosystems. This work was undertaken with the aim of studying in vitro the effect of water commonly used in agriculture on weight gain, mortality and biochemical parameters (total protein, total carbohydrates, lipids total and CAT) as biomarkers of oxidative stress, in a model biological Aporrectodea trapezoides The physicochemical analysis of the soil showed that the latter is suitable for life earthworms, rich in organic matter 12.9%, of sandy-loamy texture with a neutral pH. Sewage Caused Remarkable Earthworm Weight Drops treated with wastewater compared to controls. According to our toxicity results, no significant mortality was recorded throughout the experimental period, Treatment of earthworms with wastewater has shown an increase total protein, total carbohydrates and total lipids after 72 h On the other hand, the CAT catalase activity did not show its enzymatic induction during the three treatment periods.